Morphometric Parameters of the Corneal Flap after FemtoLASIK Using Various Femtosecond Laser - A. V. Doga; I. A. Mushkova; A. D. Semenov; A. N. Karimova; E. V. Kechin; I. N. Shormaz (Oftalʹmologiâ)
Purpose: to make a comparison of the corneal flap parameters after the FemtoLASIK procedure using femtolaser systems Femto Visum (Russia) and Femto LDV Z6 (Switzerland).Patients and methods. The study was carried out in 192 eyes from 192 patients with mild and moderate myopia who had undergone  FemtoLASIK prodecure. Group 1 (Femto Visum) included 98 eyes (n  = 98) on which flap were formed using femtolaser Femto Visum  (“Optosystems”, Russia), group 2 (Femto LDV Z6) included 94 eyes (n = 94) and Femto LDV Z6 was used (“Ziemer Ophthalmic  Systems AG”, Switzerland). The Femto Visum and Femto LDV Z6  groups were comparable in terms of pre-operative data (age, sex,  corneal curvature, central corneal thickness, sphere, cylinder,  spherical equivalent) (p > 0.05). The intended flap thickness was  100 μm and diameter was 9.0 mm in both groups. One month after  surgery the achieved flap thickness in the horizontal and vertical  meridians (14 measurement points) and the flap diameter in the  horizontal meridian were measured using Visante OCT (Carl Zeiss,  Germany), also we determined the shape of the flap and the mean  deviation of the values from morphometric parameters of the corneal flap relative to the intended values.Results. In group 1 (Femto Visum), the total average thickness of  the flap was 98.89 ± 3.96 μm with the mean deviation 2.91 ± 2.91  μm, the mean flap diameter was 8.96 ± 0.13 mm with the mean  deviation 0.11 ± 0.07 mm, in group 2 (Femto LDV Z6) the same  parameters were 99.11 ± 3.89 μm, 2.99 ± 2.64 μm and 8.91 ± 0.14 mm, 0.13 ± 0.10 mm, respectively. The configuration of the corneal  flap was uniform in both groups. For all studied parameters it was no any statistically significant differences between studied groups (p >  0.05, Student’s t-test).Conclusions. The Femto Visum and Femto LDV Z6 femtolaser systems allow to shape the uniform and highly predictable corneal  flap morphometric parameters, similar measurements were obtained from both systems.